Assessment of meteorological drought using Standard Precipitation Index model (SPI) in Herat, Afghanistan - Alkozay, Arif (International Journal of Multidisciplinary Approach Research and Science, 2024)
Assessing drought is a crucial component of effective drought risk management, stemming from diminished precipitation relative to the historical average, which subsequently impacts soil moisture and water reservoirs. The standard precipitation index (SPI) is commonly used to capture temporal and spatial variations. This research aims to evaluate the intensity, frequency, and duration of meteorological drought using SPI with time scales of 1, 3, 6, and 12 months in Herat Province, Afghanistan. The study encompasses 6 gauging stations with a 43-year record period in the region. The results show that with an increase in the time scale, the duration and frequency of drought increase. Additionally, the study reveals that the common extreme drought year for all stations was the year 2001, but the most extreme occurred in the year 2009 with an intensity two times greater than that of the year 2001. Due to the discrepancy of drought occurrence in each station, the findings suggest that for better drought management in the country, it is essential to analyze droughts in each local location. Over the past 43 years, the Cheldkhtaran station experienced the highest proportion of time in drought, accounting for 28.5%. Similarly, the Khosh Rabat station experienced droughts for 26.4%, the Nazdik-i-Herat station for 27.7%, the Pul-i-Hashemi station for 23.6%, and the Rabat-i-Akhund station for 26.9% of their respective time in the past 43 year.